Miniaturization of microwave bandpass filters using nanostructured and bulk YBa2Cu3O7−δ superconductor films - Jasim, Saleh Eesaa (2018)
In Internet of Things (IoT) era, wireless communication is an essential technology to enable connection between electronic time devices. Microwave bandpass filters are essential components in the wireless communication systems and microwave circuits to enable selection of high-fidelity signals within the broadcast radio frequency (RF). The conventional microwave filters occupy large space due to consisting of several circuit components and larger sizes inevitably add up losses. Innovative approaches are therefore required to fabricate high performing microwave filters. An ideal filter is characterized by high return loss (> -10 dB), no insertion loss (~0 dB), and broad bandwidth (>1.5 GHz). This thesis describes the design and development of microwave bandpass filters characterized by high return loss (-30 dB), small insertion loss (up to -2 dB), small size (100 mm2) and broad bandwidth (1.5 GHz) using high-temperature superconducting YBa2Cu3O7-δ (HTS YBCO). The microwave bandpass filter circuit is designed using the computer-aided design (CAD) software using finite element modelling employing known as High Frequency Structural Simulator (HFSS) software. A cascaded of 4 parallel-coupled lines is adopted to realize so that the miniaturized microwave bandpass filter operating at higher frequency using a substrate of high dielectric constant (ɛ = 24) such as LaAlO3 substrate. The HTS YBCO is synthesized by electrospinning process and solid-state reaction method. Using electrospinning, YBCO nanomaterials in five morphologies, i.e. nanorods (NRs), nanogarlands (NGs), nanoparticles (NPs), nanohierarchical (NH) and agglomerated nanoparticles (ANPs) are prepared using polyvinylpyrrolidone polymer (PVP) of different molecular weights and weight ratios (relative to the precursors). The synthesized HTS YBCO samples are characterized using Thermogravimetric Analysis (TGA/DSC), X-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), and Brunauer–Emmett–Teller (BET) specific surface area techniques. The structural characterizations of YBCO samples have demonstrated the orthorhombic crystal structure with reported lattice parameters. The superconducting properties of the materials are determined by alternating current susceptibility (ACS) measurements. The YBCO bulk sample prepared by solid-state reaction shows the higher Tc (i.e. 92 K). On the other hand, the Tc values of electrospun samples are ranging between 82K and 90K. The BET measurements of YBCO sample (ANPs) showed 6.8 m2/g with Tc = 84 K. Meanwhile, NGs shows the highest surface area (7.06 m2/g) and intermediate Tc (88 K). The surface area of bulk sample presents 1.0 m2/g with high (Tc 92 K). Based on the simulated design, the microwave bandpass filters are developed using spun-coated thin films on LaAlO3 substrate. The microwave properties of filter circuits were experimentally determined by the Vector Network Analyser (VNA) at room temperature (300 K) and in liquid nitrogen (77 K). The solid-state filter showed higher return loss (i.e. -22 dB) at operating frequency of 9.7 GHz and bandwidth of 1.5 GHz, which is consistent with the simulation results. However, the electrospun YBCO filters have exhibited lower performance than conventional powders derived through solid state reaction due to the nano-structural properties of the former which leads to high surface resistance. Nevertheless, the best result has been achieved using the solid state reacted YBCO and the novel design. The results embodied in this thesis is therefore giving promising directions to develop next generation microwave filters.